Health-related quality of life among patients undergoing hemodialysis in a tertiary center in South Kerala - L. Manju; Jigy Joseph (Elsevier, 2024)
Introduction: Health-related quality of life is essential for evaluating treatment quality in chronic diseases, providing valuable patient perspectives for medical decisions. Chronic kidney disease and end-stage renal disease significantly affect Health-related quality of life. The study aimed to assess the Health-related quality of life and the factors affecting it in end-stage renal disease patients on maintenance hemodialysis. Methods: A cross-sectional study was conducted in a tertiary care center in Kerala from November 2021 to December 2022.A validated Kidney Disease Quality of Life in the local language Malayalam was used for data collection. Patients over the age of 18 who have end-stage renal disease and have been on maintenance dialysis for at least 3 months and agreed to participate were included in the study by consecutive sampling method. Results: Among the 124 patients studied, the physical component had the lowest mean score (38.11 ± 20.87), mental component displayed a higher score compared to the physical (47.33 ± 16.88), indicating moderate level of mental well-being. Kidney Disease Component Summary had the highest mean score (61.73 ± 9.42).Younger patients had better mental-health related quality of life, while age did not significantly affect physical or disease-specific health related quality of life. Gender differences appeared, with males reporting higher physical-health related quality of life. Discussion and conclusion: The study highlights the quality of life and its association with socio-personal variables. To enhance the well-being of end-stage renal disease patients in Kerala, public health initiatives should prioritize elderly females with limited education, tailoring interventions to address their specific issues.